2009
DOI: 10.1007/s12274-009-9095-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Ex situ doping of ZnTe and ZnSe nanostructures with extreme aspect ratios

Abstract: We report synthesis windows for growth of millimeter-long ZnTe nanoribbons and ZnSe nanowires using vapor transport. By tuning the local conditions at the growth substrate, high aspect ratio nanostructures can be synthesized. A Cu-ion immersion doping method was applied, producing strongly p-type conduction in ZnTe and ionic conduction in ZnSe. These extreme aspect ratio wide-bandgap semiconductors have great potential for high density nanostructured optoelectronic circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
1
11
0
1
Order By: Relevance
“…Simultaneously, the photocurrent spikes generated by the system and the time dependency of the response signal satisfy the Hebbian STDP rule . Additionally, as promising candidates, nitrides (e.g., AlN), tellurides (e.g., ZnTe) and other compounds (e.g., AgI, manganite) have also been explored for memristor applications.…”
Section: Active Materials and Dopantsmentioning
confidence: 98%
“…Simultaneously, the photocurrent spikes generated by the system and the time dependency of the response signal satisfy the Hebbian STDP rule . Additionally, as promising candidates, nitrides (e.g., AlN), tellurides (e.g., ZnTe) and other compounds (e.g., AgI, manganite) have also been explored for memristor applications.…”
Section: Active Materials and Dopantsmentioning
confidence: 98%
“…Este material puede cristalizar en dos tipos de estructuras cristalinas: Zincblenda (cúbica) y Wurtzita (hexagonal), cuyos sistemas cristalinos asociados a estas estructuras son Fm< 43 > y Pmc< 186 >, respectivamente. La fabricación de ZnSe en forma de película delgadas se ha realizado a partir de diferentes técnicas: haces moleculares (Molecular Beam Epitaxy, MBE) [8], deposito químico en fase vapor con precursores orgánico-metálicos (Metal Organic Chemical Vapor Deposition, MOCVD) [9], spray pirolisis [10], evaporación asistida por láser pulsado [11], métodos químicos [12] y pulverización catódica [13]. Este trabajo presenta el estudio de las propiedades opto-eléctricas (respuesta espectral y temporal) y morfológicas de las películas delgadas de ZnSe en función de la temperatura de sustrato, las cuales fueron depositadas sobre sustratos de vidrio por evaporación térmica de alto vacío.…”
Section: Introductionunclassified
“…26 Yim et al also reported the ex-situ Cu doping of ZnTe nanoribbons by a similar Cu-ion immersion doping method. 27 Recently, Li et al reported in-situ N doping of ZnTe nanoribbons with improved p-type conductivity by using a gaseous NH 3 dopant source. 28 However, to the best of our knowledge, there is no report on phosphorus doping in ZnTe nanowires.…”
Section: Introductionmentioning
confidence: 99%